Factors Determining the Involvement of Women in Income Generating Activities: A Case Study in Pokhara Metropolitan City, Nepal - Tiwar, Surendra (Kalika Journal of Multidisciplinary Studies, 2022)
Women’s participation in income-generating activities (IGAs) appears to be limited in communities of Nepal owing to a variety of socio-cultural and socio-economic variables. Despite the deliberative efforts by governmental and different developmental agencies for the empowerment of women to be participated actively in income generating activities (IGAs), it is unclear yet what factors stimulate Nepalese women’s engagement in various earning activities. Against this backdrop, the purpose of this study was to investigate the variables that stimulate the participation of Nepalese women in IGAs in the Pokhara Metropolis. For this purpose, a systematic survey form was used to gather data. A total of 130 individuals were interrogated, comprising 65 women engaged in IGAs (selected purposively) and 65 women, who are not involved in IGAs (selected conveniently and purposively) for making the study more comprehensive. A Binary logistic regression model was applied for finding the factors determining the involvement of women in IGAs. The result of the analysis revealed that literacy status, occupational status and monthly income of family affect the women’s involvement in IGAs significantly while age, marital status, caste, family type, number of a family member and age at first marriage do not have any effect on it. The study suggests that it is imperative to make women aware about the importance of involvement in IGAs as this will help them to be self-dependent. The Government of Nepal should focus on women’s education to ensure the necessary knowledge and entrepreneurial skills needed for their effective participation in income-generating activities.